Thyroglossal cyst in elderly: a rare cause of inspiratory stridor - Agrawal, Animesh; Baisakhiya, Nitish; Sharma, Harshita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Thyroglossal cyst is the most common congenital anterior neck swelling in childhood. Commonly present as painless swelling in the 2nd decade of life but the cases are reported in the elderly age group also. It represents the persistent epithelial tract from the foramen cecum to the thyroid gland. Clinically can be diagnosed and can be differentiated with other mid-line swelling by movement with the protusion of tongue. It is usually related to the hyoid bone and may be supra-hyoid, infra-hyoid, lower part of the midline or rarely lingual in position. Ultrasonography is the investigation of choice for this cystic condition. It is safe, economical and easily available investigation among all the radiological study. MRI is helpful to diagnose cervical extension and lingual cyst. Inspite of close relation to the laryngeal structure it rarely present as laryngeal mass and causes stridor or sleep apnea as in our case. Classic Sistrunk procedure is the treatment of choice for the condition. Endoscopic CO2 Laser is useful in situation where only intraoral cyst present without cervical extension. Marsupialization is reserved for lingual cyst especially in Neonate. We are reporting this case which was present in the elderly and reported with long standing anterior neck swelling with inspiratory stridor on lying down position.